2021
DOI: 10.1021/acsenvironau.1c00030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphonate Herbicides on the Secretions of Plant-Beneficial Compounds by Two Plant Growth-Promoting Soil Bacteria: A Metabolomics Investigation

Abstract: Plant growth-promoting rhizobacteria (PGPR) that colonize plant roots produce a variety of plant-beneficial compounds, including plant-growth regulators, metal-scavenging compounds, and antibiotics against plant pathogens. Adverse effects of phosphonate herbicides, the most extensively used herbicides, on the growth and metabolism of PGPR species have been widely reported. However, the potential consequence of these effects on the biosynthesis and secretion of PGPR-derived beneficial compounds still remains to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Explicitly, isolates S36 and S37 showed the highest sequence similarity with P. megaterium and P. arybhattia respectively. In correspondence, a number of studies have showed that, bacterial strains in the genus Pristia are versatile in degrading pesticides including atrazine (Abd Rani et al 2022 ), chlorpyrifos (Varghese et al 2022 ) and benzoate (Esikova et al 2021 ) using diverse metabolic pathways in mineralizing toxins and pesticides (Li et al 2022 ). Moreover, Pailan et al ( 2015 ) reported that B. arybhattia SanPS1 could tolerate chlorpyrifos and parathion at concentrations of 500 μg mL −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Explicitly, isolates S36 and S37 showed the highest sequence similarity with P. megaterium and P. arybhattia respectively. In correspondence, a number of studies have showed that, bacterial strains in the genus Pristia are versatile in degrading pesticides including atrazine (Abd Rani et al 2022 ), chlorpyrifos (Varghese et al 2022 ) and benzoate (Esikova et al 2021 ) using diverse metabolic pathways in mineralizing toxins and pesticides (Li et al 2022 ). Moreover, Pailan et al ( 2015 ) reported that B. arybhattia SanPS1 could tolerate chlorpyrifos and parathion at concentrations of 500 μg mL −1 .…”
Section: Discussionmentioning
confidence: 99%